Interhemispheric water exchange in the Atlantic Ocean - Goni, G. J.; Malanotte-Rizzoli, Paola, 1946- (Elsevier oceanography series, 2003)
Recent results from modeling and observational studies demonstrate that the tropical Atlantic is a critical region for processes that maintain the meridional overturning circulation, such as cross-equatorial exchanges, and for sea surface temperature variability that impacts on climate variability of the coupled tropical ocean/atmosphere system. The theme of this book is the inter-hemispheric and inter-gyre exchanges of heat, salt and fresh water, while its goal is to improve the knowledge of the tropical Atlantic dynamics and how it affects the global ocean.